Acknowledgment of excellence - Siti Sarah, Mohamad Rajimi (2017)
A total of 166 UMP staff received their award for service excellent performance in UMP throughout 2016. They were celebrated in an event of Quality and Innovation Day (Majlis Hari Kualiti dan Inovasi 2017) that was held today at Astaka Hall, UMP Gambang Campus. Event was officiated by Chairman of UMP Board of Director, Dato’ Sri Mohd. Hilmey Mohd Taib and was attended by UMP Vice Chancellor Professor Dato’ Dr. Daing Nasir Ibrahim, Deputy Vice Chancellor (Academic & International), Prof. Dato’ Dr. Rosli Mohd Yunus and Deputy Vice Chancellor (Research & Innovation) Prof. Dr. Mashitah Yusof.